2016
DOI: 10.1007/s00125-016-4095-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the obesity-risk gene FTO and the dopamine D2 receptor gene ANKK1/TaqIA on insulin sensitivity

Abstract: Aims/hypothesis Variations in FTO are the strongest common genetic determinants of adiposity, and may partly act by influencing dopaminergic signalling in the brain leading to altered reward processing that promotes increased food intake. Therefore, we investigated the impact of such an interaction on body composition, and peripheral and brain insulin sensitivity. Methods Participants from the Tübingen Family study (n = 2245) and the Malmö Diet and Cancer study (n = 2921) were genotyped for FTO SNP rs8050136 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 53 publications
(73 reference statements)
1
40
0
2
Order By: Relevance
“…More specifically, in a sample of 2245 individuals the FTO SNP rs 805136 only influenced body fat content, waist-to-hip ratio, insulin sensitivity and fasting insulin if they also carried the at-risk allele of the ANKK1 SNP [141]. Strikingly, a similar effect was observed with insulin action in the DRD2 rich caudate nucleus: FTO influenced insulin sensitivity only in A1 allele carriers.…”
Section: Fto Gene Variantsmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, in a sample of 2245 individuals the FTO SNP rs 805136 only influenced body fat content, waist-to-hip ratio, insulin sensitivity and fasting insulin if they also carried the at-risk allele of the ANKK1 SNP [141]. Strikingly, a similar effect was observed with insulin action in the DRD2 rich caudate nucleus: FTO influenced insulin sensitivity only in A1 allele carriers.…”
Section: Fto Gene Variantsmentioning
confidence: 99%
“…First, variations in the fat mass and obesity-associated (FTO) gene are the strongest polygenic determinants of adiposity [32] and inactivation of this gene impairs DRD2-dependent neurotransmission and function in rodents [33] and DRD2-dependent learning in humans [34]. Second, the TaqIA RFLP, which is associated with variation in DRD2 receptor density [3538], was recently shown to interact with an FTO gene variant to influence adiposity, central and peripheral insulin resistance and DRD2-dependent learning [34, 39]. In both studies the influence of FTO on these phenotypes was found to be either greater in individuals who also possessed a copy of the TaqIA at-risk allele or dependent upon individuals also having this genotype.…”
Section: Why Drd2?mentioning
confidence: 99%
“…Individuals carrying risk alleles are at risk of weight gain related to hypo-responsivity to food cues or taste receipt within dorsal striatal regions (caudate) [85, 86], whereas in non-carriers, hyper-responsivity promotes obesity risk. While the interpretation of such findings as a deficit in experienced reward has been debated [87, 88], inherited variability in dopamine-dependent neural signaling clearly influences components of CNS appetite regulation and obesity risk directly [89, 8, 90] and via interactions with other risk genes [84, 91]. …”
Section: Evidence That Response To Visual Food Cues Is An Inherited Tmentioning
confidence: 99%
“…Moreover, each individual inherits a blend of risk and protective alleles, which could also increase variability within samples enrolled in single-gene association studies. Moreover, these studies might also be misleading when genetic effects are modified by other inherited factors [84, 91], sex, BMI [82, 81], or the particular loci under investigation [92]. Finally, normal weight adults with high-risk genotypes may have neural responsiveness that differs from high-risk allele carriers who are vulnerable to weight gain, and some results are derived from exclusively normal weight samples [93, 82, 84].…”
Section: Evidence That Response To Visual Food Cues Is An Inherited Tmentioning
confidence: 99%
“…112 Other studies have shown association between FTO and ANKK1 variants with decreased D2 receptor density in the nucleus accumbens. 113 …”
Section: Brain Disease and Neuronal Behaviormentioning
confidence: 96%